Assessment of risk factors for cystic periventricular leukomalacia. Issue 11 (13th September 2020) - Kurimoto, Tomonori; Ibara, Satoshi; Kamitomo, Masato; Tokuhisa, Takuya; Maeda, Takatsugu; Maede, Yoshinobu; Ishihara, Chie; Naito, Yoshiki; Hirakawa, Eiji; Yamamoto, Tsuyoshi
Abstract: Aim: Periventricular leukomalacia (PVL) is an important cause of cerebral palsy in premature infants, and cystic PVL is the most serious form of the disease. The risk factors for cystic PVL in singleton fetuses at a gestational age of <35 weeks are unclear. Methods: This study included 2013 singleton birth infants delivered at a gestational age of <35 weeks in Kagoshima City Hospital between 2006 and 2017. The findings for 30 infants with cystic PVL were compared with those for 63 matched control infants by gestational age and birth weight. Results: The cystic PVL was associated with increased incidence of recurrent late deceleration (L/D) (43.4% vs. 15.9%, P = 0.004) and loss of variability (LOV) (10.0% vs. 0.0%, P = 0.03) in fetal heart rate monitoring and late‐onset circulatory dysfunction (LCD) (33.3% vs. 11.1%, P = 0.02). Logistic regression analysis revealed that recurrent L/D (odds ratio [OR] = 3.57, 95% confidence interval [CI]: 1.29–10.15, P = 0.01) and LCD (OR = 3.41, 95% CI: 1.09–11.04, P = 0.03) were risk factors associated with cystic PVL. LOV was not included in the multivariate analysis as there were too few cases in both the cystic PVL and control groups. Conclusion: Recurrent L/D, LOV and LCD are strongly associated with cystic PVL. In cases of fetal acidosis related to recurrent L/D or loss of variability, cystic PVL may occur.